Pengaruh Brand Image dan Service Quality Terhadap Customer Loyalty - Nabila Risty Rizkita; Osly Usman (Peneliti.net, 2026)
This study analyzes the influence of Brand Image and Service Quality on Customer Loyalty, mediated by Customer Satisfaction, at Pelindo Residence & Convention. Using an explanatory quantitative approach with 125 respondents and SEM-PLS analysis, the study finds that Brand Image and Service Quality significantly impact Customer Satisfaction, while Brand Image and Customer Satisfaction positively influence Customer Loyalty. A key novelty of this research reveals a consumer behavior anomaly: Service Quality has no direct influence on loyalty, requiring Customer Satisfaction as a full mediator. Conversely, Brand Image possesses a psychological strength that independently drives loyalty without the need for mediation. Practically, hotel management must recalibrate operational services (SOP) into emotional interventions focused on guest satisfaction, while maintaining brand image equity as a primary strategy for customer retention amidst intense post-pandemic industry competition.